Answer:
2 and 3 are same since in both the cases we need to square 2 only not the negative 1 in it
1 is not same to 2 and 3 since in 1 we need to square 2 and negative 1 in it also.
Explanation:
We are given the three expressions different from each other
We are supposed to find what may be same or different.
1)
![(-2)^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ymm3w3s43s07qmtf0nii1ptwfznd6tw6oj.png)
![\Rightarrow (-1)^2 * (2)^2\\\Rightarrow -1 * -1 * 2 * 2 \\\Rightarrow 4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3gcj66smo1dnvlu0fvkgg1x6x4pjomqk8r.png)
2)
![-2^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xnq0h3a9x3qvlo6fz9ssrkfx7lj4utiony.png)
![\Rightarrow -1 * 2^2\\\Rightarrow -1 * 2 * 2 \\\Rightarrow -4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lhufasvy1951gx3xvoefdmn6yp5tifnad4.png)
3)
![-(2)^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/m8cod5hhkxzgwug0awbvybhc8uikfufkjw.png)
![\Rightarrow -1 * (2)^2\\\Rightarrow -1 * 2 * 2 \\\Rightarrow -4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/fudc33nnantlzexd7anwwkcmr7o6ojb5x5.png)
Now 2 and 3 are same since in both the cases we need to square 2 only not the negative 1 in it
1 is not same to 2 and 3 since in 1 we need to square 2 and negative 1 in it also.